2020
DOI: 10.1101/2020.02.18.20024281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-adjusted estimation of the number of Coronavirus Disease 2019 cases in Wuhan, China

Abstract: An outbreak of clusters of viral pneumonia due to a novel coronavirus (2019-nCoV / SARS-

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
223
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(234 citation statements)
references
References 22 publications
3
223
1
7
Order By: Relevance
“…9 These values showed that SARS-CoV-2 is highly contagious and it was projected that without any control measures the infected population would exceed 200 000 in Wuhan by the end of February 2020. 10 Other researchers estimated infected numbers of 191 529 (95% CI: 132 751 to 273 649) by 4 February 2020. 11 In the absence of an effective vaccine, 12 social distancing measures were needed to prevent transmission of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…9 These values showed that SARS-CoV-2 is highly contagious and it was projected that without any control measures the infected population would exceed 200 000 in Wuhan by the end of February 2020. 10 Other researchers estimated infected numbers of 191 529 (95% CI: 132 751 to 273 649) by 4 February 2020. 11 In the absence of an effective vaccine, 12 social distancing measures were needed to prevent transmission of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the meta-data of five countries' evacuation action from January 29 to February 2, Zhao et al (2020) estimated that almost 110,000 (CI: 40,000-310,000) individuals were infected with SARS-CoV-2 in Wuhan by February 2. Wang et al (2020) estimated 4 phases divided by the dates when various levels of prevention and control measures were taken in effect in Wuhan, the number of infections would reach the peak 58, 077-84,520 or 55,869-81,393 in late February.…”
Section: How Many Wuhan Residents Were Infected With Sars-cov-2mentioning
confidence: 99%
“…The first human cases of COVID-19, the disease caused by the novel coronavirus causing COVID-19, subsequently named SARS-CoV-2 were first reported by officials in Wuhan City, China, in December 2019 [1]. Retrospective investigations by Chinese authorities have identified human cases with onset of symptoms in early December 2019 [2]. While some of the earliest known cases had a link to a wholesale food market in Wuhan, some did not.…”
Section: Introductionmentioning
confidence: 99%